Replacement Analysis of Official Vehicles at Universitas Negeri Padang with Electric Vehicles - Firdaus, Pangeran Albari Ramadino; Milana, Milana; Saputra, Hendra Dani; Rifdarmon, Rifdarmon (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
Replacement analysis is used to evaluate whether the currently used asset needs to be replaced with a newer and more economically efficient one. This study aims to determine the feasibility of replacing the official service vehicles at Universitas Negeri Padang from conventional vehicles to electric vehicles based on an economic analysis. Data on official service vehicles were collected from the facilities and infrastructure division of Universitas Negeri Padang, while data on electric vehicles were obtained through a literature review. Data processing was conducted using the Equivalent Uniform Annual Cost (EUAC) method. The results indicate that replacing the official service vehicles at Universitas Negeri Padang from conventional vehicles to electric vehicles is not yet feasible.